(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
This article is the result of research and discussions by the Group Imagens Políticas das Artes Carnavalescas, linked to the Imagens Políticas das Artes Carnavalescas research line of the Postgraduate Program in Performing Arts (PPGAC) at the State University of Santa Catarina (UDESC). We carried out a historical survey of the use of lighting in samba schools and will point to some parades from the year 2023 in the Rio carnival, whose lighting was a relevant factor in the Rio de Janeiro Special Group Samba Schools Competition. Our objective is to guide the debate on possible new directions in carnival art based on the study of stage lighting at carnival.